DAMPAK ALIH FUNGSI LAHAN HUTAN MENJADI LAHAN SERAI WANGI TERHADAP SOSIAL EKONOMI MASYARAKAT DIKECAMATAN MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN - Deja Capria Nita; Rozana Eka Putri; Trina Febriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the Impact of Forest Land Conversion into Agricultural Land on the Socio-Economics of the Community in Mapat Tunggul Selatan District, Pasaman Regency. The type of research used is a mix method combining two research methods, namely quantitative and qualitative. This research was conducted in Mapat Tunggul Selatan District, Pasaman Regency. Research informants used Random Sampling, with Mapat Tunggul Selatan Dalam Community leaders as key informants. Data collection and analysis were carried out using NVivo software version 15 and the Rikter Scale. The research results show: 1) The impact of forest land conversion to citronella plantations on community social life is influenced by social changes, where people have begun to abandon shifting cultivation practices, regular, routine, and seasonal work patterns, close, and harmonious relationships between residents, disrupted community access due to land conversion that causes landslides and floods, and the influx of residents. 2) The impact of forest land conversion to citronella plantations on the community's economy is influenced by changes in income, adequate livelihoods, ample market access, feasible job opportunities, and improved economic conditions. 3) The spatial distribution of land converted from forest to citronella cultivation in Mapat Tunggul Selatan District generally covers farmer-owned land with an area varying between 0.5 and 5 hectares, with the majority of farmers cultivating 1.5-2 hectares for citronella. This land management is carried out individually and includes land clearing processes such as clearing and clearing before planting. Keywords: Land Conversion, Lemongrass Land, Community Socio-Economics